2012
DOI: 10.1242/dev.070110
|View full text |Cite
|
Sign up to set email alerts
|

The Prdm family: expanding roles in stem cells and development

Abstract: SummaryMembers of the Prdm family are characterized by an Nterminal PR domain that is related to the SET methyltransferase domain, and multiple zinc fingers that mediate sequence-specific DNA binding and protein-protein interactions. Prdm factors either act as direct histone methyltransferases or recruit a suite of histone-modifying enzymes to target promoters. In this way, they function in many developmental contexts to drive and maintain cell state transitions and to modify the activity of developmental sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
274
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(283 citation statements)
references
References 174 publications
(308 reference statements)
4
274
1
4
Order By: Relevance
“…Prdm proteins are a family of epigenetic zinc-finger transcriptional regulators with important roles in cell differentiation and diseases (Fog et al, 2012;Hohenauer and Moore, 2012). In mouse and zebrafish embryos, Prdm12 is expressed in specific regions of the developing brain, in spinal cord p1 progenitors and in dorsal root and trigeminal ganglia (Kinameri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prdm proteins are a family of epigenetic zinc-finger transcriptional regulators with important roles in cell differentiation and diseases (Fog et al, 2012;Hohenauer and Moore, 2012). In mouse and zebrafish embryos, Prdm12 is expressed in specific regions of the developing brain, in spinal cord p1 progenitors and in dorsal root and trigeminal ganglia (Kinameri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on Blimp1 and its human ortholog PRDI-BF1 (PRDM1 -Human Genome Nomenclature Committee) have demonstrated that Prdm1 represses multiple target genes through the recruitment of various histone modifying proteins, including histone methyltransferases (Gyory et al, 2004;Ancelin et al, 2006) and histone deacetylases (Yu et al, 2000), or through binding to the Groucho family of co-repressors (Ren et al, 1999). Whereas other members of the PRDM family have intrinsic methyltransferase activity through the PR/SET domain (Hohenauer and Moore, 2012), it appears that Prdm1 lacks this activity (Gyory et al, 2004). This suggests that Prdm1 might depend largely on binding partners to regulate its target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Both seq and ttk have previously been linked to the Notch pathway (Guo et al, 1996;Brenman et al, 2001;Althauser et al, 2005;Jordan et al, 2006;Andrews et al, 2009). Comparing with mammalian proteins, Seq is most homologous to Prdm10, a member of the positive regulatory domain (PRDM) family, many of which are involved in embryonic development and Notch signaling (Hohenauer and Moore, 2012;Zannino and Sagerstrom, 2015). Because of the connections between seq, ttk, the PRDM family and Notch signaling, we pursued the role of seq with the aim of gaining further insight into the temporal activation of Notch signaling required for precise type I>0 daughter switches.…”
Section: /P27mentioning
confidence: 99%